Extraction of oleoresin from Zingiber zerumbet Rhizome: Comparative study on yield, zerumbone and curcumin content - Hasham@Hisam, Rosnani; Sulaiman, Norsaupiah; Sarmidi, Mohamad Roji; Abdul Aziz, Ramlan; Che Pa, Nasrul Fikry (Universiti Malaysia Sabah, 2003)
Extraction of oleoresin involves several processing parameters that can alter the nutritional and chemical properties of the samples. Processing parameters studied in this research were blanching treatments, types of solvent and time of extraction. The effect of the processing parameters on the oleoresin yield, zerumbone and curcumin content of the Zingiber zerumbet was determined. The type of solvent was found as the most influential parameter that affects the yield of oleoresin and its zerumbone and curcumin content. Ethanol found to be the best solvent. The highest yield of oleoresin, zerumbone and curcumin was obtained after 18 hours of extraction. The processing parameters were observed to promote the increment of yield of oleresin and zerumbone and curcumin content.